2016
DOI: 10.15640/jaes.v4n2a1
|View full text |Cite
|
Sign up to set email alerts
|

Distichlis palmeri: Perennial Grain Yields under Saline Paddy-style Cultivation of Grains on Seawater

Abstract: All our major grain crops are glycophytic grasses that require irrigation with quality water, annual tillage and reseeding of non-salinized soils. Farming of perennial halophytic crops has the potential to circumvent these restrictive issues. The present study reports perennial yields and proximate analysis of Distichlis palmeri grain. D. palmeri is a C4 dioecious halophytic grass endemic to the Sea of Cortez where native Cocopah gathered its 8 mm long grain as a wild harvest. We grew first generation D. palme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Despite the small sample size of the study reported here, the results are consistent with the findings of several past studies [32][33][34]. For example, a study that collected basil, lettuce, barramundi and water from 6 laboratory aquaponics-systems over 118 days failed to detect generic E. coli, E. coli O157:H7, or Salmonella in any of the samples [34].…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Despite the small sample size of the study reported here, the results are consistent with the findings of several past studies [32][33][34]. For example, a study that collected basil, lettuce, barramundi and water from 6 laboratory aquaponics-systems over 118 days failed to detect generic E. coli, E. coli O157:H7, or Salmonella in any of the samples [34].…”
Section: Resultssupporting
confidence: 91%
“…This previous study, like the study reported here, found similar levels of coliforms (between 13 and 1820 CFU/100-g; calculated using data reported in the study; [34]). Also similar to the study reported here, a study that assessed microbial contamination on lettuce and water samples collected from two Puerto Rican hydroponic facilities failed to detect Salmonella [32]. Interestingly, the low levels of microbial contamination reported here and in previous aquaponics and hydroponics studies, contrasts to the substantially higher levels of microbial contamination reported by studies conducted in conventional production environments.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations